Development of flipbook media to improve personification writing skills - Anisa Nur Suprihatindariani; Sukarir Nuryanto (Universitas Muhammadiyah Malang, 2025)
Writing must pay attention to spelling, diction, and the use of figures of speech to produce quality written works. Personification figures of speech play an important role in writing skills because they can help writers create more lively and imaginative writing, as well as increase the appeal of written works to readers. By giving human characteristics to objects or animals, writers can make written works more interesting and easier to understand. However, during observations and interviews, it was still found that the writing skills of personification figures of speech at SDN Jatibarang 01 Central Java were still low because the use of media that was only limited to books made students bored when studying. The provision of interactive media is very much needed to overcome this problem. Flipbook is one of the interactive media, easy to use and its contents can be adjusted to learning materials such as personification figurative language materials and animations can be added according to the contents so that they are more harmonious and interesting. The purpose of this study was to produce flipbook media and test its effectiveness in helping to improve writing skills, especially in writing personification figures of speech. The researcher used the Research and Development model ADDIE research type. It can be seen from the results of the trial that the flipbook was said to be very feasible by the media expert validator with a score of 93.33% and the material validator with a score of 90%. In the T test, the researcher used a paired sample t-test and the test results showed a sig. (2-tailed) value of 0.00 so that the value <0.05 can be seen that there is a significant difference in the pre-test and post-test of the use of flipbook media. In the N-Gain test, the N-Gain value of 0.4291 is in the moderate category, which shows an increase after using the media, as seen from the average pre-test value which from 72 to 84.. It can be concluded that flipbooks are effective in improving personification writing skills.